How Russia shaped the modern world : from art to anti-semitism, ballet to bolshevism - Marks, Steven G. (Steven Gary), 1958- (Princeton, N.J. : Princeton University Press, 2003)
This sweeping history tells the fascinating story of how Russian figures, ideas, and movements changed our world in dramatic but often unattributed ways.
On Europe's periphery, Russia was an early modernizing nation whose troubles stimulated intellectuals to develop radical and utopian alternatives to Western models of modernity. These provocative ideas gave rise to cultural and political innovations that were exported and adopted worldwide. Wherever there was discontent with modern existence or traditional societies were undergoing transformation, anti-Western sentiments arose. Many people perceived the Russian soul as the antithesis of the capitalist, imperialist West and turned to Russian ideas for inspiration and even salvation.
Steven Marks shows that in this turbulent atmosphere of the past century and a half, Russia's lines of influence were many and reached far. Russia gave the world new ways of writing novels. It launched cutting-edge trends in ballet, theater, and art that revolutionized contemporary cultural life. The Russian anarchist movement benignly shaped the rise of vegetarianism and environmentalism while also giving birth to the violent methods of modern terrorist organizations. Tolstoy's visions of nonviolent resistance inspired Gandhi and the U.S. Civil Rights movement at the same time that Russian anti-Semitic conspiracy theories intoxicated right-wing extremists the world over. And dictators from Mussolini and Hitler to Mao and Saddam Hussein learned from the experiments of the Soviet regime.
Moving gracefully from Moscow and St. Petersburg to Beijing and Berlin, London and Luanda, Mexico and Mississippi, Marks takes us on an intellectual tour of the Russian exports that shaped the twentieth century. The result is a richly textured and stunningly original account of the extent to which Russia--as an idea and a producer of ideas--has contributed to the making of the modern world. Placing Russia in its global context, the book betters our understanding of the anti-Western strivings that have been such a prominent feature of recent history.
1. Organizing Revolution: The Russian Terrorists -- 2. Kropotkin's Anti-Darwinian Anarchism -- 3. Dostoevsky's Messianic Irrationalism -- 4. Tolstoy and the Nonviolent Imperative -- 5. Destroying the Agents of Modernity: Russian Anti-Semitism -- 6. Conveying Higher Truth Onstage: Ballet and Theater -- 7. Abstract Art and the Regeneration of Mankind -- 8. The Dream of Communism -- 9. Communism and the New Forms of Dictatorship.
Includes bibliographical references (p. [337]-379) and index.
Donation of Anatole Shub
Keywords: Civilization, Modern -- Russian influences; Russia -- Civilization -- 1801-1917.; Soviet Union -- Civilization